1890 Ky. Acts 618 - (:unkn) unknown (My University, 1890)
An Acts to Establish a City Government for the Town of North Middle-Town, ch 327 Article III§7: The council should have the power tor regulate and restrain the firing and concealed carry of firearms.
Keywords: CARRY - CONCEALED; DISCHARGE